1998
DOI: 10.1007/s003810050259
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of hyperglycaemia in paediatric head injury

Abstract: Fifty children with head injury were evaluated in an attempt to establish a correlation between post-traumatic hyperglycaemia and long-term outcome. In all the patients, the blood glucose level was measured on admission and on the days following the trauma (threshold of normal value set at 150 mg/dl). Hyperglycaemia was seen more frequently in children with severe head injury than in those with mild and moderate head injury. It was present in 87.5% of the patients with a Glasgow Coma Score (GCS) < or =8 (the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 15 publications
3
41
1
2
Order By: Relevance
“…Other studies in children with traumatic brain or head injury have also shown an association between poor neurological outcome and elevated admission blood glucose. 24,[26][27][28] Brain trauma patients with permanent neurological deficits and in a vegetative state were found to have significantly higher admission blood glucose concentrations than children with good neurological recovery or minimal deficits. In addition, the development of inpatient hyperglycemia in children with extensive burn injuries, covering more than 60% of total body surface area, was found to increase the risk of bacteremia and fungemia, reduce skin graft adhesion, and increase the mortality rate.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies in children with traumatic brain or head injury have also shown an association between poor neurological outcome and elevated admission blood glucose. 24,[26][27][28] Brain trauma patients with permanent neurological deficits and in a vegetative state were found to have significantly higher admission blood glucose concentrations than children with good neurological recovery or minimal deficits. In addition, the development of inpatient hyperglycemia in children with extensive burn injuries, covering more than 60% of total body surface area, was found to increase the risk of bacteremia and fungemia, reduce skin graft adhesion, and increase the mortality rate.…”
Section: Discussionmentioning
confidence: 97%
“…Even though many markers associated with neuronal and glial injury, hypoxia, and inflammation have been studied, currently there is no reliable and practical biochemical marker of head injury 5,11,26,28) . Only two markers seem to have a diagnostic adjunct in adults : neuron-specific enolase (NSE) and S100B protein 5,7,10,13,14,17,28,[34][35][36] .…”
Section: Proposal For a Panel Of Biomarkers Including Serum Osmolaritmentioning
confidence: 99%
“…However, high blood glucose is common in acutely ill neurological patients, even in non-diabetics ones. A consensus regarding the cut-off blood glucose level that would be related to a poor prognosis in children and adolescents with head trauma is still lacking, which makes the comparison of different studies particularly troublesome [3][4][5][6][7][8][9] .…”
mentioning
confidence: 99%
“…Some authors believe that patients with hyperglycemia generally have a low Glasgow Coma Scale (GCS) score [3][4][5][6] , poor neurological prognosis (based on GCS) and a history of severe trauma with significant brain injury 6,7 . It is well known that such acute hyperglycemia is a result of catecholamine' effects 8,9 .…”
mentioning
confidence: 99%